Molecular markerbased genetic linkage map of a diploid banana population (Musa acuminata Colla) - Mbanjo, E.; Tchoumbougnang, F.; Mouelle, A.; Oben, J.; Nyine, M.; Dochez, C.; Ferguson, Morag E.; Lorenzen, J.H. (Springer, 2012)
A well-saturated genetic linkage map is valuable for fundamental and applied genetic research. Genetic linkage maps of two half-sib diploid banana populations were constructed using allele-specific-polymerase chain reactions (AS-PCRs), diversity array technology (DArT), and simple sequence repeat (SSR) markers. Molecular maps were produced for each parent using the pseudo-testcross mapping strategy. The first maternal map (6142-1, 81 individuals) consisted of 231 markers divided as followed: 121 DArT, 106 SSR and 4 AS-PCR markers in 15 linkage groups (LGs) covering 670 cM. The second maternal map (6142-1-S, 58 individuals) contained a total of 152 markers including 71 DArTs, 79 SSRs, and 2 AS-PCRs mapped to 16 LGs that spanned 698 cM. The combined paternal map (139 individuals) comprised 316 markers (196 DArTs, 117 SSRs and 3 AS-PCRs) distributed over 15 LGs with a total map length of 1,004 cM. While distorted segregation of some markers was observed in all maps, this was much more frequent for the male parent. Homology between maps was assessed using common markers. While there was generally good congruity with regard to marker order across maps, incongruity in other cases may reflect chromosomal rearrangement events such as inversions, translocations, or deletions. The new banana map can provide a better understanding of the Musa genome and could be used for the identification of economically important traits and improvement of breeding strategies.